PERAN KEPALA MADRASAH DALAM MENGEMBANGKAN KOMPETENSI SOSIAL GURU - Arsudin, Muhammad (LPPM Universitas Islam 45, 2024)
This study aims to determine the role of Madrasah Principal as an innovator in improving the social competence of teachers, the efforts made and the inhibiting factors found in Madrasah Ibtidaiyah Ikhwanul Muslimin Bojonggede, Bogor Regency. This research uses a qualitative approach with data collection techniques through interviews, observation and documentation. The subject of this research is the Head of Madrasah, with sources deputy Head of Madrasah, teachers and supervisors of Madrasah Ibtidaiyah Bojonggede Bogor Regency. The results showed that the role of Madrasah head in developing teachers' social competence is as an innovator in every learning activity through innovation or renewal that follows the development of learning technology and information. Efforts made by the Head of Madrasah Ibtidaiyah Ikhwanul Muslimin Bogor Regency in improving the performance of PAI teachers include including teachers in teacher working groups and subject teacher deliberation forums with the costs incurred being the obligation of the school to bear it. Factors inhibiting the role of Madrasah Principal as a manager in improving teacher competence include bureaucratic factors, budget, infrastructure, communication, teacher motivation.